Childhood dental pain and anxiety: is there a relationship? (Research, Society and Development, 2022)
To assess whether there is an association between pain and anxiety in children during dental treatment. This is a longitudinal observational study, in which pain and anxiety were evaluated in 18 children aged 6 to 10 years attended in two dental consultations at the Pediatric Dentistry clinic of UNIFAL-MG. Before each consultation, the presence of pain was evaluated using the Wong Baker FACES Scale (WBFS) and anxiety using the Facial Image Scale (FIS) and the Modified Come Picture Test (VTP-M). Data were analyzed using the Mann-Whitney and Spearman test (P